Aspects of speech‐language abilities are influenced by MECP2 mutation type in girls with Rett syndrome. (26th November 2014) - Urbanowicz, Anna; Downs, Jenny; Girdler, Sonya; Ciccone, Natalie; Leonard, Helen
<x xml:space="preserve">Abstract</x> This study investigates relationships between methyl‐CpG‐binding protein 2 gene (MECP2) mutation type and speech‐language abilities in girls with Rett syndrome. Cross‐sectional data on 766 girls, aged 15 years and under, with genetically confirmed Rett syndrome was obtained from the Australian Rett Syndrome Database (ARSD) (n = 244) and the International Rett Syndrome Phenotype Database (InterRett) (n = 522). Relationships between MECP2 mutation type and age of regression in speech‐language abilities, and the level of speech‐language abilities before and after this regression were investigated. The females had a median age of 4.95 years in the ARSD and 5.25 years in InterRett. The majority (89%, 685/766) acquired speech‐language abilities in the form of babble or words at some point in time. Of those who acquired babble or words, 85% (581/685) experienced a regression in these abilities. Those with a p.Arg133Cys mutation were the most likely to use one or more words, prior to (RRR = 3.45; 95% CI 1.15–10.41) and after (RRR = 5.99; 95% CI 2.00–17.92), speech‐language regression. Girls with Rett syndrome vary in their use of speech and language, and in their experience of speech‐language regression and these variations are partly explained by genotype. © 2014 Wiley Periodicals, Inc.